Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan PT. Pattindo Malang - Rizal Ula Ananta Fauzi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2018)
The background of this study aims to determine the effect of transformational leadership, transactional leadership and organizational culture on the performance of employees of PT. PATTINDO Malang. This research uses survey method with questionnaire as data collection tool. Population in this research is all employees of PT. PATTINDO Malang which amounted to 207 people. Samples taken as many as 67 employees with simple sampling random sampling technique. Data obtained through questionnaires that tested the validity and reliability using the product moment correlation formula and cronbach's alpha. Data analysis using multiple regression analysis, F test, t test, determination coefficient test, dominant test and accompanied by classical assumption test. The results showed that: (1) Transformational Leadership, Transactional Leadership and Organizational Culture simultaneously influence the significance of employee performance PT. PATTINDO Malang. It is proven from F test to get the value of F_ (count) of 19.330 received 5% significance level (p <0.05) and H_ (2) accepted. (2). Transformational leadership positively affects the performance of employees of PT. PATTINDO Malang. This is evident from the Test of t obtained the value of t_ (count) of 2.283 received 5% significance level (p <0.05) and H_ (2) accepted. (3) Transactional leadership influence negatih on employee performance PT. PATTINDO Malang. This is evident from the t test obtained t_ (count) value of 0.489 rejected 5% significance level (p <0.05) and H_ (2) rejected (4). Organizational culture has a positive effect on the performance of employees of PT. PATTINDO Malang. This is evident from the Test of t obtained the value of t_ (count) of 4.127 received 5% significance level (p <0.05) and H_ (2) accepted (5) Organizational culture dominant influence on employee performance PT. PATTINDO Malang, This is proven by the value of the largest Standardized Coefficients beta value of 0.493.